Fotocatalytic degradation of methylene blue by floating TiO2-coconut fiber - Sugandi, Didiek; Wahyuni, Nelly; Rahmalia, Winda (Acta Chimica Asiana, 2024)
Indonesia's expanding industrial sector has resulted in an increase in the use of dyes. Methylene blue (MB), a dye used in the batik and textile industries, has the potential to be detrimental to people and the environment. Recent research indicates that the TiO2 photocatalyst has the ability to reduce MB. TiO2 transported in coconut fiber can improve illumination in the photocatalysis process. The purpose of this study is to examine the properties and activity of a TiO2-coconut fiber photocatalyst. SEM-EDX was used to characterize the morphology and composition of floating catalysts, and Fourier transform infrared (FT-IR) was used to characterize the functional groups. At 120 minutes, TiO2-coconut fiber photocatalysis with a mass ratio of 20:80 w/w demonstrated the maximum degradation of 62.72%. The SEM-EDX data demonstrate the morphology of TiO2 distribution on the surface of coconut fiber, which is distinguished by the presence of the main elements O, Ti, and C. The FT-IR study results demonstrate a shift and decrease in Ti-O absorption intensity from 756,09 cm1 to 721,38 cm1, indicating the presence of Ti-O-C bonds. It is hoped that this research will be useful in the treatment of MB in textile industry waste or other organic waste.